On heat transfer to pulsatile flow of a two-phase fluid - A. K. Ghosh; S. P. Chakraborty (International Journal of Mathematics and Mathematical Sciences)
The problem of heat transfer to pulsatile flow of a two-phase fluid-particle system contained in a channel bounded by two infinitely long rigid impervious parallel walls has been studied in this paper. The solutions for the steady and the fluctuating temperature distributions are obtained. The rates of heat transfer at the walls are also calculated. The results are discussed numerically with graphical presentations. It is shown that the presence of the particles not only diminishes the steady and unsteady temperature fields but also decreases the reversal of heat flux at the hotter wall irrespective of the influences of other flow parameters.